Model Predictive Current Control Fed by Single- Phase Indirect Matrix Converter (SP-IMC) with Reactive Power Minimization - Hazrul, Mohamed Basri; Kasumawati, Lias; Yonis M Yonis, Buswig; Saad, Mekhilef (Semarak Ilmu Publishing, 2026)
This study presents a predictive current control and reactive power minimization strategy for a two-level single-phase indirect matrix converter (SP-IMC). The proposed control strategy takes advantage of the discrete nature of the system to predict the future load current and reactive power behaviour to perform switching optimization based on a minimum cost function criterion. Forward Euler’s approximation is used based on unitary power factor condition, minimum reactive power, and minimum load current harmonic content (THD%). An optimized rectifier switching strategy was also conducted to ensure positive fictitious dc-link voltage at any instant. Several robustness tests have been conducted at a laboratory scale and the experimental results of the proposed control are provided in this paper. From the experimental results, the Forward Euler’s approximation exhibits good load current reference tracking and reactive power minimization ability.